Mandibular Two Mini Implants Overdenture Using Magnetic Attachments: A Case Report - Miyayasu, Anna; Kanazawa, Manabu; Asami, Mari; Thuy, Vo Lam; Thu, Khaing Myat; Shimada, Ryo; Minakuchi, Shunsuke (UI Scholars Hub, 2017)
Many patients with an edentulous mandible struggle to use complete dentures. The instability of such dentures, caused by the lack of retention, often causes discomfort, as well as functional and psychosocial problems, which can be significantly improved using implant overdentures with retentive attachments. This case report describes a successful case of a mandibular implant overdenture using two mini implants and magnetic attachments for an elderly edentulous patient. Case Report: A 62-year-old female with a thin mandibular bone ridge presented with complaints of pain caused by an unstable and unretentive complete mandibular denture. This patient received two mini implants (diameter: 2.6 mm; length: 12 mm) with magnetic attachments. After three months, magnetic assemblies with magnetic attraction of 400 gf were incorporated into the intaglio surface of her mandibular overdenture. At 11 months, magnetic attraction was changed from 400 gf to 600 gf to provide a stronger magnetic force for improving the retention of this denture. Conclusion: Based on a two-year follow-up period, the mandibular two mini implants overdenture with magnetic attachments was successful in improving the patient’s general satisfaction with her dentures.